2011
DOI: 10.1186/ar3402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atorvastatin on coronary calcifications and myocardial perfusion defects in systemic lupus erythematosus patients: a prospective, randomized, double-masked, placebo-controlled study

Abstract: IntroductionMortality in systemic lupus erythematosus (SLE) patients is influenced by an increased occurrence of severe cardiovascular complications. Statins have been proven to protect a wide spectrum of SLE patients from these complications. This study was conducted to determine the possible efficacy of atorvastatin in SLE patients as assessed by multi-detector computed tomography (MDCT)-based coronary calcium scoring and single photon emission computed tomography (SPECT) of the myocardium.MethodsSixty SLE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…At one year, atorvastatin significantly decreased coronary calcification progression (but not myocardial perfusion), lipids and C-reactive protein levels in the first trial. 3 At two years, the benefit of atorvastatin on carotid intima-media thickness was statistically significant in a post-hoc analysis of the second trial. 4 In both studies, there was no change of the SLEDAI score on atorvastatin, but the trials were not designed to assess disease flare prevention.…”
Section: Introductionmentioning
confidence: 97%
“…At one year, atorvastatin significantly decreased coronary calcification progression (but not myocardial perfusion), lipids and C-reactive protein levels in the first trial. 3 At two years, the benefit of atorvastatin on carotid intima-media thickness was statistically significant in a post-hoc analysis of the second trial. 4 In both studies, there was no change of the SLEDAI score on atorvastatin, but the trials were not designed to assess disease flare prevention.…”
Section: Introductionmentioning
confidence: 97%
“…Certain therapeutic 9 approaches, usually with statins, have been implemented for halting subclinical atherosclerosis in lupus patients with inconsistent results [12][13][14][15]. Other preventive strategies, such as ACEIs and ARBs, which have shown a significant benefit in at-risk populations [5], have not been tested in SLE patients.…”
Section: Resultsmentioning
confidence: 99%
“…We found that companion female had more diseases of the musculoskeletal system and connective tissue (44% vs. 21% in male companions; p=0.024), and they were taking more medications of the musculoskeletal system (26.2% vs. 5.4% in male companions; p=0.014), but we found no difference in diseases or treatments about mental health (Table 1). Other authors have also noted that women caregivers reported significantly more physically unhealthy days than men, and more physical morbidity (lower physical health scores, poorer physical functioning, and loss of physical strength) (29,30).…”
Section: Discussionmentioning
confidence: 99%